Taṭwīr Ta`līm al-Qirā‘ah Bi Ṭarīqah Wadhīfah al-Majmū`ah `Alā Asās al-Madkhal al-Ittiṡālī Wa Ṭarīqah at-Ta`allum at-Ta`āwunī Bi MTsN 1 Aceh Barat - Agustia Rahmaini; Syarifuddin Syarifuddin (The Department of Arabic Language Education, Pascasarjana Universitas Islam Negeri Banda Aceh of UIN Ar-Raniry Banda Aceh, Aceh, Indonesia., 2023)
The purpose of this study was to identify how to develop the learning process using the wadhifah al-majmu'ah method based on a communicative approach and cooperative learning methods in teaching reading and to identify the effectiveness of the wadhifah al-majmu'ah method to improve students' reading skills at MTsN 1 Aceh Barat and to identify teacher and student activities using the developed wadhifah al-majmu'ah method. The research method used in this research is the research and development method. The results of this research are the development of wadhifah al-majmu'ah method by observing the need and the problem and by interviewing experts, this method has ten steps in its process. The use of wadhifah al-majmu'ah method is effective in improving students’ ability to reading skills. The average value of the post-test is greater than the pre-test (82.44> 54.34), the sig. (2-tailed) 0.000 which is smaller than the significance level of 0.05, indicates that (Ha) is acceptable and (Ho) is returned. And very good result, This is proved by the direct observation of teacher activities by 90 % and student activities by 85 % indicating that they are between 81-100% In the very good category. The use of wadhifah al-majmu'ah method is effective in improving student’s ability to reading skills.